The use of Brazilian vegetable oils in nanoemulsions: an update on preparation and biological applications - Lisiane Bajerski; Luana Roberta Michels; Letícia Marques Colomé; Eduardo André Bender; Rodrigo José Freddo; Fernanda Bruxel; Sandra Elisa Haas
ABSTRACT Vegetable oils present important pharmacological properties, which gained ground in the pharmaceutical field. Its encapsulation in nanoemulsions is considered a promising strategy to facilitate the applicability of these natural compounds and to potentiate the actions. These formulations offer several advantages for topical and systemic delivery of cosmetic and pharmaceutical agents including controlled droplet size, protection of the vegetable oil to photo, thermal and volatilization instability and ability to dissolve and stabilize lipophilic drugs. For these reasons, the aim of this review is to report on some characteristics, preparation methods, applications and especially analyze recent research available in the literature concerning the use of vegetable oils with therapeutic characteristics as lipid core in nanoemulsions, specially from Brazilian flora, such as babassu (Orbignya oleifera), aroeira (Schinus molle L.), andiroba (Carapa guaianiensis), casca-de-anta (Drimys brasiliensis Miers), sucupira (Pterodon emarginatus Vogel) and carqueja doce (Stenachaenium megapotamicum) oils.